2018
DOI: 10.1371/journal.pone.0204405
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life compared between kidney transplantation and nocturnal hemodialysis

Abstract: BackgroundHealth-related quality of life (HRQOL) is an important outcome measure in patients with end-stage renal disease. HRQOL is assumed to improve with kidney transplantation and also with nocturnal hemodialysis compared to conventional hemodialysis. However, there is no evidence regarding HRQOL to support the optimal treatment choice for patients on nocturnal hemodialysis who hesitate opting for transplantation. We therefore compared HRQOL between patients who were treated with kidney transplantation or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
(30 reference statements)
2
18
1
4
Order By: Relevance
“…Compared with HD and PD groups, Tx patients signi cantly enjoyed a better quality of life and suffered less from psychological problems. The results veri ed that treatment modality was one of the most important factors affecting HRQOL psychological states of ESRD patients, and Tx was superior to the other two treatments, which was in accordance with the previous studies [2,7,[12][13][14][15][16][17][18]. It is of necessity to increase the access to Tx, whereas there still exists a remarkably prominent variation in the access to and the use of Tx across the world.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared with HD and PD groups, Tx patients signi cantly enjoyed a better quality of life and suffered less from psychological problems. The results veri ed that treatment modality was one of the most important factors affecting HRQOL psychological states of ESRD patients, and Tx was superior to the other two treatments, which was in accordance with the previous studies [2,7,[12][13][14][15][16][17][18]. It is of necessity to increase the access to Tx, whereas there still exists a remarkably prominent variation in the access to and the use of Tx across the world.…”
Section: Discussionsupporting
confidence: 90%
“…The comparison studies about HD and PD demonstrated that the HRQOL tended to be better in PD patients, especially in terms of physical component, illness intrusion, social support, social function and mental health and satisfaction with care [4,[9][10][11]. The compared HRQOL scores of Tx patients were prominently higher than those of patients under dialysis treatment in most dimensions such as role physical, bodily pain, social function, role emotional and mental health [7,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Table). For RRT treatments, KTx recipients reported higher mean generic and specific scores relative to those on dialysis [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] (S2-S4 Tables). Nagaraja et al [44] converted the SF-36 data into SF-6D utility scores and showed a similar relationship; kidney transplantation was associated with better mean SF-6D utility scores relative to HD (0.65± SD: 0.13 vs 0.52± SD: 0.11, respectively).…”
Section: The Kdqol-sf™ Toolmentioning
confidence: 99%
“…Kidney transplantation (KTx) is the most desired renal replacement therapy for patients with end-stage renal disease (ESRD), with salutary effects on quality of life (QOL) [1] and overall survival [2] compared to dialysis. However, cardiovascular disease (CVD) remains one of the leading causes of death in kidney transplant recipients (KTRs), accounting for 17% [3] of total deaths, and KTRs have an overall mortality rate at least 5–10-fold greater than the general population [4].…”
Section: Introductionmentioning
confidence: 99%